2005
DOI: 10.1529/biophysj.105.067934
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion, Mixing, and Associated Dye Effects in DNA-Microarray Hybridizations

Abstract: Typical DNA microarrays utilize diffusion of dye-labeled cDNA probes followed by sequence-specific hybridization to immobilized targets. Here we experimentally estimated the distance typical probes travel during static 16-h hybridizations. Probes labeled with Cy3 and Cy5 were individually introduced to opposite sides of a microarray with minimal convective mixing. Oppositely labeled probes diffused across the initial front separating the two solutions, generating a zone with both dyes present. Diffusion-distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Thus, only genes with a significant ''dye-bias'' will show an expression ratio (Cy3 channel intensity/Cy5 channel intensity) significantly different from 1. Dye bias could result from non-equal labeling of RNA with the two dyes, but also differences in dye-scanning detection sensitivity (Borden et al, 2005). As a result of the latter, at low signal intensities, the Cy5 channel intensity measurements will be accompanied by greater noise than low signals in the Cy3 channel (Borden et al, 2005), and the asymmetric noise of the data at the low intensity range (especially below 150) of Figure 1 likely reflects this fact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, only genes with a significant ''dye-bias'' will show an expression ratio (Cy3 channel intensity/Cy5 channel intensity) significantly different from 1. Dye bias could result from non-equal labeling of RNA with the two dyes, but also differences in dye-scanning detection sensitivity (Borden et al, 2005). As a result of the latter, at low signal intensities, the Cy5 channel intensity measurements will be accompanied by greater noise than low signals in the Cy3 channel (Borden et al, 2005), and the asymmetric noise of the data at the low intensity range (especially below 150) of Figure 1 likely reflects this fact.…”
Section: Resultsmentioning
confidence: 99%
“…Dye bias could result from non-equal labeling of RNA with the two dyes, but also differences in dye-scanning detection sensitivity (Borden et al, 2005). As a result of the latter, at low signal intensities, the Cy5 channel intensity measurements will be accompanied by greater noise than low signals in the Cy3 channel (Borden et al, 2005), and the asymmetric noise of the data at the low intensity range (especially below 150) of Figure 1 likely reflects this fact. The CG1940 reference RNA consisted of equal ratios of RNA from three 50 L lots (P50-1, P50-2, and P50-3) (see Materials and Methods Section).…”
Section: Resultsmentioning
confidence: 99%
“…5,11,21,38 While, some suggested that hybridization may be reaction limited, 11 others showed that the hybridization is reaction limited at early times when the target DNA concentration is high, but becomes diffusion limited at longer times as the target is consumed. 21,39 Experimental studies showed that continuous mixing or convective flow improved the rate and intensity of hybridization signals, suggesting that diffusion is indeed a limiting factor in surface hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…21,39 Experimental studies showed that continuous mixing or convective flow improved the rate and intensity of hybridization signals, suggesting that diffusion is indeed a limiting factor in surface hybridization. 5,40,55,56 In addition to translational diffusion, our model accounts for rotational diffusion and its effect on surface reaction and suggests that the relative contribution of these processes may depend on the size of target DNA. Our calculations showed that for short targets the reaction rate is fast and hybridization is diffusion limited but long targets are kinetically limited for the duration of the typical microarray experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, dye effects might be observed if the dye has interaction effects i.e. the gene sequence affects the labeling efficiency [141]. 48 A possible solution to the dye effect is to balance the dyes using the assumption that both channels should be equally "bright".…”
Section: Dye Effectmentioning
confidence: 99%